THE FLYSCH TROUGH THRUST IMBRICATE (BETIC CORDILLERA): A KEY ELEMENT OF THE GIBRALTAR ARC OROGENIC WEDGE - Luján M.; Crespo-Blanc A.; Balanyá J.C. (My University, 2006)
Within the Betic-Rif orogenic system, the Flysch Trough units are formed mainly by siliciclastic rocks, upper Jurassic to lower Miocene in age. In the Gibraltar Arc area, they are presently deformed as an accretionary prism, sandwiched between the fold-and thrust belt derived from the South Iberian paleomargin sedimentary series and the metamorphic rocks of the Alboran Domain, on top. In the northern branch of the Gibraltar Arc, the main tectonic unit of the Flysch Complex is the Aljibe unit, which shows a well-organized structure of thrust imbricates, post lower Burdigalian in age. In this unit, various domains separated by major accommodation zones are characterized by their structural style and vergence. This change in structural style can be explained as a consequence of the variations of rock type along the basal décollement. Finally, these thrust systems were affected by extensional, low- to medium-angle faults and large-scale very open folds, successively. The organization of the Aljibe unit fits a push-from-behind mechanism for its emplacement, in which the relatively "rigid" back stop would be represented by the Alboran Domain. With the data presented in this paper, it is definitely shown that the Aljibe unit is not "chaotic" as claimed in previous papers and that the tectonic transport direction around the Gibraltar Arc swings from a northwestward to a westward direction along its northern branch, in the vicinity of the straits. Copyright 2006 by the American Geophysical Union.
Keywords: Jurassic; Burdigalian; Mesozoic::Jurassic; Мезозой::Юрская; Cenozoic::Neogene::Miocene::Burdigalian; Кайнозой::Неоген::Миоцен::Бурдигальский